2021
DOI: 10.4314/jfas.v13i3.15
|View full text |Cite
|
Sign up to set email alerts
|

3-d modelling of electrical parameters’ effects on the heating of the base of an intense light illuminated polycrystalline silicon PV cell

Abstract: Performances of a solar cell are significantly influenced by the heating of the base. Two phenomena contribute to the heating of the base of a PV cell: the heat due to the transfer by conduction of the solar energy radiation received by the surface of the PV cell and the heat generated inside the solar cell by various phenomena related to the movement of photogenerated electrons and holes. Thus, even if the increase of the quantity of carriers leads to improve the PV cell electrical parameters, this phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…But taking into account the mode of illumination, concentrated PV cells operate under high temperatures. Thus, some authors have shown, through studies, that the elevation of temperature causes a drop in the performances of PV cells [2] [3]. Other authors are interested in the effect of light intensity on the performance of PV cells and observed that increasing the intensity of incident light improves performance of PV cell [2] [4].…”
Section: Introductionmentioning
confidence: 99%
“…But taking into account the mode of illumination, concentrated PV cells operate under high temperatures. Thus, some authors have shown, through studies, that the elevation of temperature causes a drop in the performances of PV cells [2] [3]. Other authors are interested in the effect of light intensity on the performance of PV cells and observed that increasing the intensity of incident light improves performance of PV cell [2] [4].…”
Section: Introductionmentioning
confidence: 99%